User-centered practices in the eyes of informal caregivers of in-patients with severe acquired brain injury: needs, caring experience, and satisfaction. (19th September 2021) - Girardi, Giovanna; Farnese, Maria Luisa; Scarponi, Federico; De Tanti, Antonio; Bartolo, Michelangelo; Intiso, Domenico; Formisano, Rita; Antonucci, Gabriella
ABSTRACT: Objective: This study examines the perceived needs, experience, and satisfaction of informal caregivers (ICGs) in in-hospital settings, related to their involvement in the design and delivery of services together with hospital staff, namely co-production. Design: To obtain a picture of current ICG–staff relationship, a multicenter observational study was carried out. Participants were 75 ICGs recruited in five dedicated in-patient neurorehabilitation wards. Participants answered a self-report questionnaire tapping perceived information/communication needs, emotional/social needs, and their satisfaction; family-centered practices implemented by the staff (namely involving practices and cooperative communication); and ICGs' satisfaction with the service. Results: Need satisfaction related positively to staff practices aimed at involving IGCs in treatment and training, but not in decision-making. Involving practices concerning treatment also related positively to ICGs' information/communication needs. In addition, the more the staff involved ICGs in decision-making and promoted cooperative communication regarding treatment, the more ICGs felt that their collaboration in the healthcare process was valuable. Finally, all involvement practices and cooperative communication were positively related to ICGs' overall satisfaction with the service. Conclusion: The results of the study help to identify gaps in meeting ICGs' needs and to promote strategies to implement family participation toward co-production in in-hospital settings.